2013
DOI: 10.1155/2013/707930
|View full text |Cite
|
Sign up to set email alerts
|

A C-Terminal Transmembrane Anchor Targets the Nuage-Localized Spermatogenic Protein Gasz to the Mitochondrial Surface

Abstract: Mitochondria, normally tubular and distributed throughout the cell, are instead found in spermatocytes in perinuclear clusters in close association with nuage, an amorphous organelle composed of RNA and RNA-processing proteins that generate piRNAs. piRNAs are a form of RNAi required for transposon suppression and ultimately fertility. MitoPLD, another protein required for piRNA production, is anchored to the mitochondrial surface, suggesting that the nuage, also known as intermitochondrial cement, needs to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…By contrast, mutated MLS (Phe/F to Pro/P mutation in MLS, GFP‐F/P) or MLS with the deletion of its last four amino acids (ΔLQRK) failed to bring GFP to mitochondria (Fig C). These results, in large part, match those found in recent findings by Altshuller et al . In common, we identified a functional MLS at the C‐terminus of GASZ protein, and its mutation leads to the mislocalization of GASZ from mitochondria to the cytoplasm in somatic cells.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…By contrast, mutated MLS (Phe/F to Pro/P mutation in MLS, GFP‐F/P) or MLS with the deletion of its last four amino acids (ΔLQRK) failed to bring GFP to mitochondria (Fig C). These results, in large part, match those found in recent findings by Altshuller et al . In common, we identified a functional MLS at the C‐terminus of GASZ protein, and its mutation leads to the mislocalization of GASZ from mitochondria to the cytoplasm in somatic cells.…”
Section: Resultssupporting
confidence: 91%
“…GASZ may act as a central scaffold protein to recruit these germ cell‐specific factors into close proximity at mitochondria at IMC. To support this hypothesis, multiple nuage‐associated proteins (including MIWI, DAZL, MVH, and TDRD1) have been previously identified as interacting partners for GASZ . Unlike a reported GASZ‐knockout study , GASZ and MILI proteins were still found in the GASZ Δ MLS/ Δ MLS gonocytes with the MLS deletion, and both of them displayed a diffused pattern in the cytoplasm instead of a perinuclear granular localization at mitochondria in wild‐type controls.…”
Section: Discussionmentioning
confidence: 92%
“…Notably, whether GASZ localizes mitochondria outer membrane depends on its C-terminal mitochondrial targeting sequences and is mainly co-expressed with IMC component MILI both in the gonocytes and spermatocytes, and partially co-localizes with MVH and TDRD1, indicating its enrichment in IMC. In contrast, in round spermatid, GASZ is still expressed as a granular signal in the cytoplasm partially co-staining with mitochondria, but not localized in the CB [31,46,49].…”
Section: Gaszmentioning
confidence: 80%
“…It remains unclear how IMC forms in embryonic prospermatogonia and postnatal spermatogonia to support spermatogenesis. GASZ is highly expressed at embryonic day 13.5 ( 29 ), and is the only known germ cell-specific mitochondrial protein that is expressed when IMC starts to appear and affects IMC integrity when deleted from embryonic germ cells ( 23 , 27 ). In this study, we found that GASZ formed dimers and were able to cluster mitochondria in somatic cells when no other germ cell-specific proteins were present.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few germ cell-specific proteins are known to be localized directly at mitochondria. Of these, GASZ (also called ASZ1) is found at the mitochondrial outer membrane via a C-terminal mitochondrial localization signal (MLS) ( 23 , 27 ). GASZ is a germ cell-specific protein with four Ankyrin repeats (ANK), a sterile alpha motif (SAM), and a putative basic leucine zipper domain (bZIP) ( 28 ).…”
Section: Introductionmentioning
confidence: 99%